Corruption as One of the Threats to Customs Bodies’ Information Security in the Republic of Kazakhstan - AZHIMETOV, Yerulan; SARTBAYEVA, Uldanay; ORDAYEVA, Aigul; ZIYABEKOVA, Gulnur; AZHIMETOVA, Zakhan (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
This work is dedicated to studying problems on providing information security of customs bodies in the Republic of Kazakhstan. It researches one of the main threats to the efficiency of information security – corruption. Corruption is one of the most negative factors that disrupts the activity of customs bodies from inside. Besides the general destructive impact on the system of state power, it is possible to speak about the influence of corruption on certain state institutes, organizational systems, and even their subsystems. The aim of this work is to find problems, eliminate causes and conditions that contribute to corruption crimes in the area of customs information. The work considers peculiarities and determinants of the corruption activity at the modern stage of the informatization of the customs affair, shows the specificity of destructive impact of corruptionists on objects of the information infrastructure of customs bodies. It researches the national anticorruption legislation of the Republic of Kazakhstan (RK), statutory provision of information security, the relevant legislation of member countries of the Customs Union (CU) and the Eurasian Economic Union (EEU), and the European Union, the USA and Great Britain. Special emphasis is made on the issues related to improving the work on liquidating corruption. Based on the conclusion about the need to estimate the customs corruption as a serious multifactorial threat to the information security, comprehensive measures are offered. They include the unification of technical, organizational, and statutory standards of the information security of customs bodies of CU and EEU member states, taking all efforts and using all means to reveal and prevent corruption crimes among employees of the RK customs service.